Urban Landfills and Bird Ecology: Evaluating and Protecting Migratory Birds in Tayba Al Hasanab, Khartoum, Sudan - Adam, Mutasim Essa Abdallah; Mohamed, Mawya Ahmed Elshafea (Geography, Earth Science and Environment: Research Highlights Vol. 6, 2025)
Open landfill sites, when managed properly, can become valuable feeding grounds for birds. These waste disposal areas often support a range of trophic generalist species, such as storks and scavenger raptors, which thrive on readily available food sources. Managed open landfill sites often act as critical feeding grounds for a variety of bird species. The availability of food waste at these sites creates favorable conditions for numerous generalist species, including scavengers and raptors. This study was designed to evaluate bird diversity and abundance in and around the Tayba Al Hasanab Landfill, located in Khartoum. To achieve this, a comprehensive bird census was conducted in January 2021 using a block count method. Additionally, field observations were complemented by a structured questionnaire, with interviews carried out among landfill staff and waste collectors to gather insights on bird presence, population trends, and diversity. The results of the block count revealed the presence of 23 bird species within the landfill and its surrounding areas. These species, which rely on the food resources provided by the landfill, spanned 8 avian orders and 11 families. The most abundant species observed at the site included the House Sparrow (Passer domesticus) with 97 individuals, the Black Kite (Milvus migrans) with 67 individuals, the Cattle Egret (Bubulcus ibis) with 42 individuals, and the Laughing Dove (Spilopelia senegalensis) with 36 individuals. This dominance suggests that these species are particularly adept at exploiting the landfill’s food resources. While most species identified are classified as least concern, the Egyptian Vulture (Neophron percnopterus), an endangered species, was also observed foraging at the site. Interviews revealed that bird activity was consistently noted around the landfill, with reports of both live and dead birds. Notably, fatalities included incidents such as a White Stork colliding with and being electrocuted by power lines near the landfill. These observations highlight the need for targeted surveys to identify hazardous power lines around the landfill, which could then be replaced or retrofitted with appropriate mitigation measures to prevent further bird casualties. The study also found that bird abundance and interspecific interactions varied across seasons, reflecting the dynamic nature of bird communities in response to food availability and environmental factors. Since the large presence of birds at landfills may contribute to environmental and public health challenges in urban areas, this study emphasizes the importance of monitoring seasonal fluctuations in bird populations. Moreover, it underscores the need for improved landfill management practices to minimize potential conflicts between wildlife and urban development. In conclusion, this study provides valuable insights into the bird diversity, habitat conditions, and ecological dynamics within the Tayba Al Hasanab Landfill and its surrounding environment. The availability of a constant and abundant food supply in landfills plays a crucial role in attracting numerous bird species.